2018
DOI: 10.1016/j.scitotenv.2018.06.397
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic hydroxylamine nitrification involving manganese- and iron-bearing minerals

Abstract: Hydroxylamine (NHOH) undergoes biotic and abiotic transformation processes in soil, producing nitrous oxide gas (NO(g)). Little is known about the magnitude of the abiotic chemical processes in the global N cycle, and the role of abiotic nitrification is still neglected in most current nitrogen trace gas studies. The abiotic fate of NHOH in soil systems is often focused on transition metals including manganese (Mn) and iron (Fe), and empirical correlations of nitrogen residual species including nitrite (NO), n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Our previous research has shown that NH 2 OH reacts rapidly in seawater with MnO 2 , with near-complete conversion to the potent greenhouse gas nitrous oxide (Cavazos et al 2018). We hypothesize that the high flux of nitrous oxide emissions from coastal waters, including the Louisiana Shelf (Walker et al 2010;Kim 2018), may be at least partially due to coupled biotic-abiotic reactions between Mn(III/IV)O x particles and reactive intermediates in nitrogen cycle, such as hydroxylamine similar to reactions in soils (Rue et al 2018). This hypothesis awaits further testing.…”
Section: Discussionmentioning
confidence: 91%
“…Our previous research has shown that NH 2 OH reacts rapidly in seawater with MnO 2 , with near-complete conversion to the potent greenhouse gas nitrous oxide (Cavazos et al 2018). We hypothesize that the high flux of nitrous oxide emissions from coastal waters, including the Louisiana Shelf (Walker et al 2010;Kim 2018), may be at least partially due to coupled biotic-abiotic reactions between Mn(III/IV)O x particles and reactive intermediates in nitrogen cycle, such as hydroxylamine similar to reactions in soils (Rue et al 2018). This hypothesis awaits further testing.…”
Section: Discussionmentioning
confidence: 91%
“…10,11 N 2 O can be produced from NH 2 OH by bacteria 12 and archaea, 10 and it can also be produced abiotically from interactions among these reactive intermediates and metals such as ferrous iron and manganese. 13,14 During denitrification, nitrate (NO 3 − ) is reduced step-wise to nitrogen gas (N 2 ), with nitrite (NO 2 − ), nitric oxide (NO), and nitrous oxide (N 2 O) as intermediate products. 15 Since each step of this modular process can be performed by different microorganisms, the balance between NO reduction and N 2 O reduction can result in either net production or consumption of N 2 O. Abiotic or "hybrid" (the abiotic conversion of microbially produced hydroxylamine) production of N 2 O via hydroxylamine oxidation has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple microbially mediated processes, including nitrification and denitrification, can produce N 2 O . During nitrification, ammonium (NH 4 + ) is oxidized to nitrite (NO 2 – ) and then nitrate (NO 3 – ), with reactive compounds including hydroxylamine (NH 2 OH) and nitric oxide (NO) as intermediate products. , N 2 O can be produced from NH 2 OH by bacteria and archaea, and it can also be produced abiotically from interactions among these reactive intermediates and metals such as ferrous iron and manganese. , During denitrification, nitrate (NO 3 – ) is reduced step-wise to nitrogen gas (N 2 ), with nitrite (NO 2 – ), nitric oxide (NO), and nitrous oxide (N 2 O) as intermediate products . Since each step of this modular process can be performed by different microorganisms, the balance between NO reduction and N 2 O reduction can result in either net production or consumption of N 2 O. Abiotic or “hybrid” (the abiotic conversion of microbially produced hydroxylamine) production of N 2 O via hydroxylamine oxidation has also been reported. , Understanding how different N 2 O cycling processes and the associated microbial community respond to fertilization holds the key to predicting and managing N 2 O emissions from salt marsh ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…performed laboratory experiments that showed rapid production of N2O from reaction of the phyllomanganate birnessite and NH2OH under environmental conditions. Similarly, Rue et al (2018) reacted NH2OH with pyrolusite and poorly crystalline MnO2(s) and found 82-86% transformed to N2O. Taken together, these studies suggest oxidized mineral forms of Mn also play an important role in transforming NH2OH to N2O.…”
Section: Potential Environmental Relevancementioning
confidence: 77%
“…In recent years, increasing evidence has emerged implicating abiotic processes in N2O production Zhu-Barker et al 2015). Manganese (Mn) in the form of Mn(III,IV) (oxy)(hydr)oxides (hereinafter Mn oxides) has also been linked to production of N2O both in laboratory experiments (Toyoda et al 2005;) and in soils (Bremner et al 1980;Duan et al 2020;Heil et al 2015a;Liu et al 2017b;Liu et al 2019;Rue et al 2018). While many of these studies assume Mn is in the form of either soluble Mn(II) or solid Mn oxides, in recent years soluble Mn(III) has been shown to be stabilized by ligands and may in fact represent the dominant Mn species in some environments Oldham et al 2015).…”
Section: Introductionmentioning
confidence: 99%